Professores (as) de história dialogam sobre avaliação da aprendizagem e formação: abordagem (auto)biográfica - Oliveira, Décio Luciano Squarcieri de (2011)
The present research was developed and presented to the Graduate Program in Education, Master at Education Center in the Federal University of Santa Maria, on line training Knowledge and Professional Development, aiming to learn from the thematic of the oral history and writing (auto) biographic dailies of teachers of history, as if, during their formative processes were being built the social imaginary of assessment of learning and places which these occurred. The research entitled Teachers History Discuss about Assessment of Learning and Training: an (Auto) Biographical Approach integrates the study of Education on assessment of learning, a key component of teacher education. It justifies the importance and timeliness of work, since the evaluation studies, the existing bibliographies as means of acquiring results in students performance, in education as a whole, while this research has shifted their scope to teachers of History themselves and its imaginary representations considered as responsible for their execution. The type of the present case study characterized as qualitative research used the theoretical and methodological feature of the Thematic Oral History (auto) biography mediated as a device to trigger the memories of these teachers of education in order to understand how does the assessment of learning has been represented along their formative processes, both in school and in training and further educational activities and how does this training consisted in their different places. Data collection was accessed by means of semi-structured interviews with preparing scripts for both the oral (auto) biographical narrative and also the diaries. There are reasons for the aiming for both teams of employees according to their analysis of the theoretical part of teacher education and the social imaginary. Moreover, they consider relevant dialogues between teachers and through this exchange of experiences it was possible to recognize their sensitivities and perceptions. The research has accessed various perspectives in training of meanings, many of these unknown by conventional standards / academics, identifying varieties of the assessment, from rage to anxiety, fear, nervousness, and the desire and feeling of freedom and the demand for greater teacher autonomy, both in concept and in the instruments.